Packaging adhesive film, solar cell, preparation method of solar cell and laminated cell

By using quantum dot materials, fluorescent dyes, low-dimensional perovskites and rare earth complexes and photovoltaic silicon gels in solar cell packaging films, the problem of aging of traditional packaging materials under ultraviolet irradiation is solved, and efficient utilization is achieved Ultraviolet energy, the effect of improving solar cell performance and life.

CN119451390APending Publication Date: 2025-02-14SHENZHEN PHENOSOLAR TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411646133.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional solar cell packaging materials are prone to aging under ultraviolet irradiation, resulting in a decline in battery performance. The existing light-to-film manufacturing cost is high, the application range is small, and it is easy to decompose under high temperature and high humidity conditions.

Method used

The packaging film is used to form a packaging film with photo-transfer materials including quantum dot materials, fluorescent dyes, low-dimensional perovskites and rare earth complexes and photovoltaic silicon gel as the base material, and the packaging film is formed through dispensing method, spin coating method and other processes.

Benefits of technology

The packaging film is not easily destroyed by ultraviolet rays, and can utilize ultraviolet energy to enhance the performance of solar cells, improve photoelectric conversion efficiency, extend battery life, and is suitable for packaging of a variety of different sizes and curved products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451390A_ABST
    Figure CN119451390A_ABST
Patent Text Reader

Abstract

The invention discloses a packaging adhesive film, a perovskite solar cell, a preparation method of the perovskite solar cell and a laminated cell. The packaging adhesive film comprises a substrate material and a light conversion material, the light conversion material comprises one or more of a quantum dot material, a fluorescent dye, low-dimensional perovskite and a rare earth complex, and the mass ratio of the substrate material to the light conversion material is 100: (0.1-0.5). The packaging adhesive film can be used for preparing a perovskite solar cell, has the characteristics of high plasticity, convenience in processing, ultraviolet aging resistance, water and oxygen blocking and the like, also has high Stokes shift, and can improve the PLQY characteristic. In the use process, the perovskite solar cell is not easily damaged by ultraviolet rays, and the energy of the ultraviolet rays can be utilized for improving efficiency, improving energy conversion efficiency, and improving photoelectric conversion performance, open-circuit voltage, short-circuit current and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photovoltaic technology, and in particular to a packaging film, a solar cell and a preparation method thereof, and a laminated cell. Background Art

[0002] The structure of perovskite solar cells generally includes a transparent conductive electrode, an electron transport layer, a perovskite light-absorbing layer, a hole transport layer, and a metal electrode. Perovskite tandem cells refer to perovskite layers that can be stacked on top of each other or on top of traditional crystalline silicon solar cells to form a "tandem" cell that can absorb a wider solar spectrum. According to the stacking of different materials, the technical routes of tandem perovskite solar cells include crystalline silicon / perovskite tandem cells, all-perovskite tandem cells, perovskite / CIGS tandem cells, etc. The principle of perovskite tandem cells is that the sub-cells are connected in series through a tunneling composite junction. Due to different band gaps, perovskite tandem cells can absorb sunlight of different wavelengths separately, thereby reducing the energy loss caused by electron thermal relaxation. Multi-junction tandem tandem cells prepared by stacking absorption layers with different band gaps can better utilize sunlight, thereby improving the photoelectric conversion efficiency of the battery.

[0003] In traditional technology, conventional packaging materials for solar cells include POE / EVA films, photovoltaic silicone gel, etc. During the use of solar cells, ultraviolet radiation will cause degradation and aging of the packaging materials on the surface of the cells. Long-term exposure will gradually decompose the antioxidants in the surface packaging materials of crystalline silicon solar cells, destroy the structure of the materials, and cause degradation reactions on the surface of the battery components, such as cracking and oxidation. In addition, obvious battery degradation was observed under ultraviolet radiation. Ultraviolet radiation will destroy the passivation structure on the surface of the solar cell, increase the internal resistance of the battery, and reduce the working efficiency of the battery. Based on this, the performance of perovskite solar cells is reduced during ultraviolet radiation, which is often accompanied by material migration at the interface between the hole transport layer or the electron transport layer and the perovskite, widening of the grain boundaries in the perovskite film, and decomposition of the perovskite phase, resulting in a sharp drop in performance parameters such as the battery's photoelectric conversion performance (PCE), open circuit voltage (Voc), and short circuit current (Jsc).

[0004] At present, a new type of packaging film, namely, light transfer film, has also appeared in the prior art. The light transfer film is obtained by adding wavelength conversion materials such as light conversion agents to the high-transmittance packaging film. By absorbing ultraviolet light and converting it into blue light that can generate electricity, it can ensure that the battery cells are not damaged by ultraviolet light while utilizing the energy of ultraviolet light for efficiency enhancement. However, the conversion material needs to be added to the light transfer film before preparation, and it is impossible to make different finished products by adding the conversion material later, resulting in excessively high manufacturing costs for the light transfer film; the light transfer film with the conversion material is relatively hard in physical properties, and is generally suitable for the packaging of flat and fixed-size products, but is difficult to be applied to the packaging of curved, irregular and various different-size products, resulting in a small scope of application; in addition, the light transfer film is easy to decompose carboxyl, hydroxyl, acetic acid and other substances that accelerate the decay of perovskite under high temperature and high humidity conditions, resulting in a short battery life. Summary of the invention

[0005] Based on this, it is necessary to provide a packaging film. The packaging film of the present invention can be used for solar cell packaging. The packaging film is not easily damaged by ultraviolet rays, and can utilize the energy of ultraviolet rays to increase the efficiency of solar cells.

[0006] An embodiment of the present application provides a packaging film.

[0007] A packaging film includes a base material and a light-conversion material, wherein the light-conversion material includes one or more of a quantum dot material, a fluorescent dye, a low-dimensional perovskite, and a rare earth complex, and the mass ratio of the base material to the light-conversion material is 100:(0.1-0.5).

[0008] In some embodiments, the substrate material includes photovoltaic silicone gel.

[0009] In some of the embodiments, the quantum dot material includes one or more of elemental semiconductor quantum dot material, compound semiconductor quantum dot material and heterojunction quantum dot material.

[0010] In some embodiments, the quantum dot material includes one or more of silicon quantum dot material, germanium quantum dot material, cadmium sulfide quantum dot material, cadmium selenide quantum dot material, cadmium telluride quantum dot material, zinc selenide quantum dot material, lead sulfide quantum dot material, lead selenide quantum dot material, indium phosphide quantum dot material and indium arsenide quantum dot material.

[0011] In some of the embodiments, the particle size of the quantum dot material is 2nm~20nm.

[0012] In some embodiments, the fluorescent dye includes one or more of fluorescein isothiocyanate, tetraethyl rhodamine, tetramethyl rhodamine isothiocyanate, and substances that generate fluorescence after the action of enzymes.

[0013] In some embodiments, the low-dimensional perovskite includes a perovskite based on a long-chain ammonium bromide salt doped with Sb 3+ One or more of doped zero-dimensional perovskite, thallium-doped low-dimensional perovskite and organic tin bromide hybrid perovskite.

[0014] An embodiment of the present application provides a solar cell.

[0015] A solar cell comprises the packaging adhesive film.

[0016] An embodiment of the present application provides a method for preparing a solar cell.

[0017] A method for preparing a solar cell comprises the following steps:

[0018] Prepare the main structure of solar cells;

[0019] The main structure of the solar cell is encapsulated by using an encapsulation material to form an encapsulation film to obtain a solar cell, wherein the encapsulation process includes one or more of a dispensing method, a spin coating method, a scraping method, a spray coating method and a slit coating method.

[0020] An embodiment of the present application provides a stacked battery.

[0021] A stacked battery, the stacked battery comprising a first panel, a first encapsulation film layer, a bottom battery, a composite layer, a perovskite solar cell, a second encapsulation film layer and a second panel which are sequentially stacked and connected, the bottom battery and the perovskite solar cell being connected in series, wherein at least one of the first encapsulation film layer and the second encapsulation film layer adopts the encapsulation film.

[0022] In some of the embodiments, the tandem cell includes a crystalline silicon / perovskite tandem cell, a full perovskite tandem cell, or a thin film / perovskite tandem cell.

[0023] The encapsulation film used in the above solar cells has the characteristics of strong plasticity, convenient processing, anti-ultraviolet aging, water and oxygen blocking, etc. It also has high Stokes shift and can improve PLQY (photoluminescence quantum yield) characteristics. During use, the above solar cells are not easily damaged by ultraviolet rays, and can also use the energy of ultraviolet rays to increase efficiency, improve energy conversion efficiency, and improve photoelectric conversion performance (PCE), open circuit voltage (Voc) and short circuit current (Jsc) and other performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0025] In order to more completely understand the present application and its beneficial effects, the following description will be given in conjunction with the accompanying drawings. In the following description, the same reference numerals represent the same parts.

[0026] FIG1 is a schematic diagram of a stacked battery according to an embodiment of the present invention;

[0027] Figure 2 FIG. 1 is a schematic diagram of the ultraviolet-visible light spectrum of the stacked battery according to an embodiment of the present invention.

[0028] Description of Reference Numerals

[0029] 10. Laminated cell; 100. First panel; 200. First packaging film layer; 300. Bottom cell; 400. Composite layer; 500. Perovskite solar cell; 600. Second packaging film layer; 700. Second panel. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0031] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0032] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0033] In the description of the present invention, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing the technical features, and cannot be understood as indicating or implying the relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0034] Herein, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If multiple "optional" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" item is independent of each other. In this application, descriptions such as "optionally contain", "optionally include", etc. mean "contain or not contain". "Optional component X" means that component X exists or does not exist, or means that component X is contained or not contained.

[0035] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for a broad range of quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0037] The embodiments of the present application provide an encapsulation film and a solar cell to solve at least one of the following technical problems existing in conventional solar cell encapsulation materials such as solar cell surface encapsulation materials: (1) When POE / EVA film and photovoltaic silicone gel in conventional technology are used as encapsulation films, the antioxidants therein are easily decomposed by ultraviolet radiation, causing degradation reactions such as cracking and oxidation on the surface of the battery component; (2) When a light transfer film is used in conventional technology, the conversion material needs to be incorporated before preparation and it is not possible to make different finished products by adding the conversion material later, resulting in the problem of excessively high manufacturing costs of the light transfer film; (3) The light transfer film incorporated with the conversion material has a relatively hard physical property and is difficult to be applied to the encapsulation of curved surfaces, irregular shapes and products of various sizes, resulting in the problem of too small a scope of application; (4) The light transfer film is easily decomposed under high temperature and high humidity conditions to produce substances such as carboxyl, hydroxyl, and acetic acid that accelerate the decay of perovskite, resulting in the problem of low battery life.

[0038] The solar cell prepared by the encapsulation film of the present application is not easily damaged by ultraviolet rays, and can also utilize the energy of ultraviolet rays to increase efficiency.

[0039] Exemplarily, a packaging film includes a base material and a light conversion material, wherein the light conversion material includes one or more of a quantum dot material, a fluorescent dye, a low-dimensional perovskite, and a rare earth complex, and the mass ratio of the base material to the light conversion material is 100:(0.1-0.5). The mass ratio of the base material to the light conversion material includes but is not limited to: 100:0.1, 100:0.2, 100:0.3, 100:0.4, 100:0.5, or a range between any two of the foregoing.

[0040] The above-mentioned encapsulation film has the characteristics of strong plasticity, convenient processing, resistance to UV aging, water and oxygen barrier, etc. It also has high Stokes shift and can improve PLQY characteristics. It can be used for solar cell preparation. The prepared solar cells are not easily damaged by ultraviolet rays during use, and can also utilize the energy of ultraviolet rays to increase efficiency, improve energy conversion efficiency, and improve photoelectric conversion performance (PCE), open circuit voltage (Voc) and short circuit current (Jsc) and other performance.

[0041] In some embodiments, the base material includes photovoltaic silicone gel. Photovoltaic silicone gel is a special organic silicone gel, which includes two components A and B. After the components A and B are mixed in a ratio of 1:1, they are heated and vulcanized to form a soft and transparent state. They can maintain elasticity for a long time in the temperature range of -65°C to 200°C. Photovoltaic silicone gel has excellent electrical properties and chemical stability, and is physiologically inert. The colloidal particles of photovoltaic silicone gel are fine, with a particle size of 10nm to 20nm, and have a relatively large specific surface area. The colloidal particles of photovoltaic silicone gel themselves are colorless and transparent, and do not affect the original color of the covered object or the light of the solar cell. The viscosity of photovoltaic silicone gel is low, and it can penetrate wherever water can penetrate. Therefore, it has very good dispersibility and permeability when mixed with other substances.

[0042] In some of the embodiments, the quantum dot material is a nano-semiconductor material. Quantum dot material is an important low-dimensional semiconductor material, and its dimensions in three dimensions are no greater than twice the exciton Bohr radius of its corresponding semiconductor material. Quantum dot materials are generally spherical or quasi-spherical, and their diameters are usually between 2nm and 20nm. Common quantum dot materials are composed of IV, II-VI, IV-VI or III-V elements. By applying a certain electric field or light pressure to the quantum dot material, light of a specific frequency will be emitted, and the frequency of the emitted light will change with the change of the size of the material, so by adjusting the size of the quantum dot material, the color of the light emitted can be controlled.

[0043] In some of the embodiments, the quantum dot material includes one or more of elemental semiconductor quantum dot material, compound semiconductor quantum dot material and heterojunction quantum dot material.

[0044] For example, in some embodiments, the quantum dot material includes one or more of silicon quantum dot material, germanium quantum dot material, cadmium sulfide quantum dot material, cadmium selenide quantum dot material, cadmium telluride quantum dot material, zinc selenide quantum dot material, lead sulfide quantum dot material, lead selenide quantum dot material, indium phosphide quantum dot material and indium arsenide quantum dot material.

[0045] Liri, among which Mn 2+ The doped perovskite quantum dot material has bright orange-red luminescence and a large Stokes shift. At an extremely low feed ratio, the synthesized Mn 2+ The PLQY of doped CsPbCl3 perovskite quantum dot material is as high as 87%.

[0046] In some embodiments, the quantum dot material can be further coated with silicon dioxide. After being coated with silicon dioxide, the dense double-layer protective shell further passivates the defects and traps of the quantum dot material, suppresses non-radiative recombination, and makes the PLQY of the quantum dot material reach 98%.

[0047] In some embodiments, the particle size of the quantum dot material is 2 nm to 20 nm. The particle size of the quantum dot material includes but is not limited to: 2 nm, 5 nm, 10 nm, 12 nm, 15 nm, 20 nm or a range between any two of the foregoing.

[0048] In some embodiments, fluorescent dyes are photosensitive compounds that absorb light energy of a specific wavelength and convert it into light of a longer wavelength. The unique electronic configuration of fluorescent dyes gives them unique characteristic absorption spectra (often similar to excitation) and emission spectra.

[0049] In some embodiments, the fluorescent dye includes one or more of fluorescein isothiocyanate, tetraethyl rhodamine, tetramethyl rhodamine isothiocyanate, and substances that generate fluorescence after the action of enzymes.

[0050] In some of the embodiments, PRODAN fluorescent dyes are fluorescent dyes based on naphthalene, with maximum absorption at around 350nm and maximum emission at around 450nm~490nm, and have the advantages of good photostability, high molar extinction coefficient, high photon yield, good biocompatibility, relatively less sample background interference, and good two-photon absorption performance.

[0051] In some of these embodiments, low-dimensional perovskites are generally cubic or octahedral shaped materials that have rapidly emerged due to their unique luminescence properties, including ultra-broad and high Stokes shift luminescence and pure white light chromaticity.

[0052] In some embodiments, the low-dimensional perovskite includes a perovskite based on a long-chain ammonium bromide salt doped with Sb 3+ One or more of doped zero-dimensional perovskite, thallium-doped low-dimensional perovskite and organic tin bromide hybrid perovskite.

[0053] For example, Sb 3+ Doped zero-dimensional perovskites obtain wide-spectrum fluorescence emission with high quantum yield under the Jahn-Teller effect. The strong electroacoustic coupling and soft lattice characteristics of this zero-dimensional structure are conducive to the formation of self-trapped excitons. For example, highly polar hydronium ions H3O + A novel hybrid 0D (NH4)x(OH3)3-xInCl6 perovskite with cations, doped with Sb 3+ After that, the hybrid 0D (NH4)x(OH3)3-xInCl6 single crystals exhibited efficient broadband yellow-green (550 nm) and red (630 nm) dual emission with a PLQY of 86%. The dual emission is due to Sb 3+They occupy two sites in the lattice respectively, and these two sites have different polar environments, resulting in different Stokes shift energies. 3+ In doped zero-dimensional perovskites, the zero-dimensional crystal structure is assembled into octahedrons (SnX6) and pentahedrons (SbCl5). This unique zero-dimensional structure results in a luminescence quantum yield of the crystalline material close to 100%.

[0054] For example, organic tin bromide hybrid material (C9NH 20 )2SnBr4, through the organic cationic ligand to tin bromide (SnBr4 2- ) ions are wrapped to form a zero-dimensional structure. In the hybrid crystal, the tin bromide ions form an extremely rare four-coordinate seesaw structure. This unique structure leads to its unique optical properties. The physical state is close to that of a colorless and transparent crystal, with a deep red light emission with a peak at about 695 nm, an ultra-large Stokes shift of up to 332 nm (1.63 eV), a huge half-peak width of nearly 146 nm and a deep red light quantum yield of up to 46%.

[0055] In this application, rare earth complexes (LLCs) are organic compounds with rare earth atoms as the center and several coordination bonds, which have unique and excellent optical, electrical and magnetic properties. The fluorescence luminescence mechanism of rare earth complexes is that the organic ligand sensitizes the rare earth ions and transfers the energy of its transition to the rare earth ions for luminescence. The luminescence of rare earth complexes includes four categories: the first category is the high-efficiency rare earth central ion luminescence, such as Sm 3+ (4f), Eu 3+ (4r), Tb 3+ (419), Dy 3+ (4f); The second type of low-efficiency rare earth central ion luminescence, including Pr 3+ (4f2), Nd 3+ (4f3), Ho 3+ (4f10),Er 3+ (4f11),Tm 3+ (4f12), Yb 3+ (4f13); The third type of rare earth central ions that do not produce luminescence, including La 3+ (4f10), Gd 3+ (4f7), L23 (4f14); the fourth type of ions with fd transitions; mainly Sm 2+ ,Eu 2+ , Yb 2+ , Ce 2+ Rare earth complexes have typical properties such as narrow-band spectrum, high luminescence efficiency, large Stokes shift and long luminescence lifetime.

[0056] One of them uses a novel 8-hydroxyquinoline derivative ligand to sensitize the red-emitting Eu 3+ , LLCs with excellent performance were synthesized, and a series of europium chelates were synthesized and fully characterized. The results of quantum chemical calculations show that the electron-withdrawing substituents on the phenol ring of 8-hydroxyquinoline can effectively increase the energy gap of the ligand. By screening ligands and optimizing the structure of the complex, anhydrous EuL6 was obtained, and the PLQY value reached 0.84. TGA and UV aging tests showed that this complex has excellent thermal stability and photostability. The excitation spectrum band is distributed in the 250nm~470nm region depending on the medium and sample thickness.

[0057] An embodiment of the present application provides a solar cell.

[0058] A solar cell comprises the above-mentioned packaging film.

[0059] A method for preparing a solar cell comprises the following steps:

[0060] Prepare the main structure of solar cells;

[0061] The solar cell body is packaged with a packaging material to form a packaging film to obtain a solar cell, wherein the packaging process includes one or more of a dispensing method, a spin coating method, a scraping method, a spray coating method and a slit coating method.

[0062] The above-mentioned solar cell can be a crystalline silicon cell or a perovskite solar cell.

[0063] An embodiment of the present application provides a method for preparing a perovskite solar cell.

[0064] In this article, unless otherwise stated, each reaction step may be carried out in the order described herein or may not be carried out in the order described herein. For example, other steps may be included between each reaction step, and the order of the reaction steps may also be appropriately swapped. This can be determined by the technician based on common knowledge and experience. Preferably, the reaction method herein is carried out sequentially.

[0065] A method for preparing a perovskite solar cell comprises the following steps:

[0066] Prepare the main structure of the perovskite solar cell 500;

[0067] The main structure is encapsulated with an encapsulation material to form an encapsulation film to obtain a perovskite solar cell 500, wherein the encapsulation process includes one or more of a dispensing method, a spin coating method, a scraping method, a spray coating method, and a slit coating method.

[0068] In some of the embodiments, the main structure of the perovskite solar cell 500 includes a conductive glass layer, a hole transport layer, a perovskite photoactive layer, an electron transport layer and a metal electrode.

[0069] The method for preparing the main structure of the perovskite solar cell 500 comprises the following steps:

[0070] S1. Forming a hole transport layer on a glass substrate.

[0071] S2. Preparing a perovskite photoactive layer on the hole transport layer, wherein when preparing the perovskite photoactive layer, the perovskite precursor solution contains a passivating agent.

[0072] S3. Preparing an electron transport layer on the perovskite photoactive layer.

[0073] S4. Preparing a metal electrode on the electron transport layer.

[0074] In some of the embodiments, the method for preparing the main structure of the perovskite solar cell 500 further includes the following steps: after preparing the electron transport layer, preparing a hole blocking layer on the electron transport layer, and preparing the metal electrode on the hole blocking layer.

[0075] In some of the embodiments, the method for preparing the main structure of the perovskite solar cell 500 further includes the following steps: before preparing the hole transport layer, preparing a NiOx nanoparticle layer on the conductive glass layer, and then preparing the hole transport layer on the NiOx nanoparticle layer, and the NiOx nanoparticle layer is composited with the hole transport layer.

[0076] An embodiment of the present application provides a stacked battery 10 .

[0077] A laminated battery 10 includes the above-mentioned packaging film or the above-mentioned solar cell.

[0078] In some of these embodiments, the solar cell may be a perovskite solar cell 500 .

[0079] In some embodiments, as shown in FIG1 , the stacked cell 10 includes a first panel 100, a first encapsulation film layer 200, a bottom cell 300, a composite layer 400, a perovskite solar cell 500, a second encapsulation film layer 600, and a second panel 700, which are sequentially stacked and connected, and the bottom cell 300 is connected in series with the perovskite solar cell 500. At least one of the first encapsulation film layer 200 and the second encapsulation film layer 600 uses the above-mentioned encapsulation film.

[0080] In some embodiments, the first packaging film layer 200 and the second packaging film layer 600 are both made of the above-mentioned packaging film.

[0081] In some embodiments, the bottom cell 300 includes a crystalline silicon cell, a CdTe cell, a CIGS cell, a III-V cell, or a GaAs cell.

[0082] In some embodiments, the first panel 100 and the second panel 700 may be photovoltaic glass panels respectively.

[0083] In some of the embodiments, the stacked cell 10 includes a crystalline silicon / perovskite stacked cell, a full perovskite stacked cell, or a thin film / perovskite stacked cell.

[0084] In some of the embodiments, the structure of the perovskite solar cell 500 includes a conductive glass layer, a hole transport layer, a perovskite photoactive layer, an electron transport layer, and a metal electrode.

[0085] Example 1

[0086] This embodiment provides a stacked battery.

[0087] As shown in FIG1 , the stacked cell 10 includes a first panel 100, a first encapsulation film layer 200, a bottom cell 300, a composite layer 400, a perovskite solar cell 500, a second encapsulation film layer 600 and a second panel 700 which are sequentially stacked and connected, and the bottom cell 300 is connected in series with the perovskite solar cell 500. Among them, the first encapsulation film layer 200 and the second encapsulation film layer 600 both use the above-mentioned encapsulation film. The bottom cell 300 is a crystalline silicon cell. The main structure of the perovskite solar cell 500 includes a conductive glass layer, a hole transport layer, a perovskite photoactive layer, an electron transport layer and a metal electrode.

[0088] The method for preparing the stacked battery of this embodiment comprises the following steps:

[0089] A crystalline silicon cell is obtained as a bottom cell 300, and a composite layer 400 and a perovskite solar cell 500 are sequentially prepared on the bottom cell 300; the bottom cell 300, the composite layer 400 and the perovskite solar cell 500 are encapsulated as a whole between a first panel 100 and a second panel 700 through a first encapsulation film layer 200 and a second encapsulation film layer 600.

[0090] The thickness of the first panel 100 and the second panel 700 are 50 mm respectively. The thickness of the first encapsulation film layer 200 and the second encapsulation film layer 600 are 10 mm respectively. The thickness of the conductive glass layer is 1 mm, the thickness of the hole transport layer is 10 nm, the thickness of the perovskite photoactive layer is 50 nm, the thickness of the electron transport layer is 10 nm, and the thickness of the metal electrode is 10 nm. The preparation material of the electron transport layer is PCBM, the preparation material of the hole transport layer is 2PACZ ([2-(9H-carbazole-9-yl)ethyl]phosphonic acid), and the molecular structure of the perovskite photoactive layer is ABX3, where A is a methylamine cation (MA + ); B is lead ion (Pb 2+ ); X is I - .

[0091] The encapsulation film includes a base material and a light-conversion material, the base material includes photovoltaic silicone gel, and the light-conversion material includes silicon quantum dot material.

[0092] Example 2

[0093] This embodiment provides a stacked battery.

[0094] The stacked cell of this embodiment is substantially the same as that of Embodiment 1, except that, in this embodiment, the mass ratio of the base material of the encapsulation film to the light conversion material is 100:0.5.

[0095] Example 3

[0096] This embodiment provides a stacked battery.

[0097] The stacked battery of this embodiment is basically the same as that of Embodiment 1, except that, in this embodiment, the encapsulation film includes a base material and a photoconversion material, the base material includes photovoltaic silicone gel, and the photoconversion material includes fluorescein isothiocyanate.

[0098] Example 4

[0099] This embodiment provides a stacked battery.

[0100] The laminated battery of this embodiment is basically the same as that of embodiment 1, except that, in this embodiment, the encapsulation film includes a base material and a light conversion material, the base material includes photovoltaic silicone gel, and the light conversion material includes Sb 3+ Doped zero-dimensional perovskite.

[0101] Example 5

[0102] This embodiment provides a stacked battery.

[0103] The stacked cell of this embodiment is substantially the same as that of Embodiment 1, except that, in this embodiment, the encapsulation film comprises a base material and a photoconversion material, the base material comprises photovoltaic silicone gel, and the photoconversion material comprises a rare earth complex.

[0104] Comparative Example 1

[0105] The comparative example provides a stacked battery.

[0106] The stacked cell of the comparative example is substantially the same as that of Example 1, except that, in this comparative example, the encapsulation film comprises a base material, and the base material comprises photovoltaic silicone gel.

[0107] Comparative Example 2

[0108] The comparative example provides a stacked battery.

[0109] The stacked cell of the comparative example is substantially the same as that of Example 1, except that, in this comparative example, the mass ratio of the base material of the encapsulation film to the light conversion material is 100:0.05.

[0110] Comparative Example 3

[0111] The comparative example provides a stacked battery.

[0112] The stacked cell of the comparative example is substantially the same as that of Example 1, except that, in this comparative example, the mass ratio of the base material of the encapsulation film to the light conversion material is 100:0.8.

[0113] Comparative Example 4

[0114] The comparative example provides a stacked battery.

[0115] The stacked cell of the comparative example is substantially the same as that of Example 1, except that, in this comparative example, the mass ratio of the base material of the encapsulation film to the light conversion material is 100:2.

[0116] The performance tests were performed on the stacked batteries in Examples 1 to 5 and Comparative Examples 1 to 4, respectively. The test results are shown in Table 1.

[0117] Table 1

[0118]

[0119] As can be seen from Table 1, the encapsulation films in Examples 1 to 5 include a base material and a light conversion material. The encapsulation films have the characteristics of strong plasticity, convenient processing, resistance to ultraviolet aging, water and oxygen blocking, etc., have a high Stokes shift, and can improve the PLQY characteristics. The prepared laminated battery is not easily damaged by ultraviolet rays during use, and can also utilize the energy of ultraviolet rays for efficiency enhancement, and has high performance such as energy conversion efficiency, open circuit voltage (Voc) and short circuit current (Jsc).

[0120] The encapsulation film of Comparative Example 1 does not contain light conversion materials, and its energy conversion efficiency, open circuit voltage (Voc) and short circuit current (Jsc) are relatively low.

[0121] In Comparative Example 2, the content of the photoconversion material is low, therefore, its PLQY characteristics and Stokes shift are worse than those of Example 1, and its energy conversion efficiency, open circuit voltage (Voc) and short circuit current (Jsc) are all lower than those of Example 1.

[0122] In comparative examples 3 and 4, the content of the photoconversion material is too high, and when the ultraviolet light absorption reaches saturation, there is almost no improvement in the battery efficiency, which only increases the production cost of the entire battery. If the added photoconversion material is a type that can absorb part of the visible light, a high content may lead to a decrease in battery efficiency.

[0123] from Figure 2 It can be seen from the UV-visible light spectrum that in addition to absorption in the UV band, fluorescein also has obvious absorption in the visible light region of 420nm-470nm, which will lead to a reduction in the amount of visible light incident on the perovskite active layer, especially for high doping levels, which will significantly affect the battery efficiency; quantum dots and rare earth complexes only absorb in the UV band, and high doping levels will not have an adverse effect on the light absorption of the perovskite active layer.

[0124] In summary, in the packaging of the perovskite solar cell 500 or the stacked cell 10 of the present application, the composite material formed by mixing photovoltaic silicone gel + light conversion material is used as the packaging film, which has the following technical effects:

[0125] (1) The combination materials of the encapsulation film are varied. By screening the material combination, the absorption spectrum and excitation spectrum of the encapsulation film can be adjusted. By controlling the amount of photoconversion material added and the type of material added, a larger PLQY and a larger Stokes shift can be achieved.

[0126] (2) The encapsulation film is highly efficient and has a long lifespan, which can effectively protect the battery components from running efficiently and extend the service life of the battery components.

[0127] (3) Photovoltaic silicone gel has the advantages of high transmittance, wide transmittance range and low attenuation in post-packaging testing. In view of the different wavelengths and peaks of radiation received by solar cells, photovoltaic silicone gel is combined with different photoconversion materials to achieve more effective protection and higher photoconversion efficiency.

[0128] (4) The amount of photoconversion material in the encapsulation film is small and highly efficient. Only a very small amount of photoconversion material is needed, with a mass ratio of 0.1%~0.5%. The photoconversion material is evenly mixed with the photovoltaic silicone gel to achieve the maximum PLQY and a larger Stoke's shift.

[0129] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0130] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0131] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A packaging film, characterized in that: It includes a base material and a light conversion material, wherein the light conversion material includes one or more of a quantum dot material, a fluorescent dye, a low-dimensional perovskite and a rare earth complex, and the mass ratio of the base material to the light conversion material is 100:(0.1-0.5).

2. The packaging film according to claim 1, characterized in that: The substrate material includes photovoltaic silicone gel.

3. The packaging film according to claim 1, characterized in that: The quantum dot material includes one or more of element semiconductor quantum dot material, compound semiconductor quantum dot material and heterojunction quantum dot material.

4. The packaging film according to claim 1, characterized in that: The quantum dot material includes one or more of silicon quantum dot material, germanium quantum dot material, cadmium sulfide quantum dot material, cadmium selenide quantum dot material, cadmium telluride quantum dot material, zinc selenide quantum dot material, lead sulfide quantum dot material, lead selenide quantum dot material, indium phosphide quantum dot material and indium arsenide quantum dot material.

5. The packaging film according to claim 1, characterized in that: The particle size of the quantum dot material is 2nm~20nm.

6. The encapsulation film according to any one of claims 1 to 5, characterized in that: The fluorescent dye includes one or more of fluorescein isothiocyanate, tetraethyl rhodamine, tetramethyl rhodamine isothiocyanate and substances that generate fluorescence after being acted on by enzymes.

7. The encapsulation film according to any one of claims 1 to 5, characterized in that: The low-dimensional perovskite includes perovskite doped with long-chain ammonium bromide salt, Sb 3+ One or more of doped zero-dimensional perovskite, thallium-doped low-dimensional perovskite and organic tin bromide hybrid perovskite.

8. A solar cell, characterized in that: The encapsulation film comprises the encapsulation film according to any one of claims 1 to 7.

9. A method for preparing a solar cell, characterized in that: The steps include: Prepare the main structure of solar cells; The main structure of the solar cell is encapsulated by using an encapsulation material to form an encapsulation film to obtain a solar cell, wherein the encapsulation process includes one or more of a dispensing method, a spin coating method, a scraping method, a spray coating method and a slit coating method.

10. A laminated battery, characterized in that: The stacked battery comprises a first panel, a first encapsulation film layer, a bottom battery, a composite layer, a perovskite solar cell, a second encapsulation film layer and a second panel which are sequentially stacked and connected, wherein the bottom battery and the perovskite solar cell are connected in series, wherein at least one of the first encapsulation film layer and the second encapsulation film layer adopts the encapsulation film according to any one of claims 1 to 7.